MANAGEMENT OF CITRUS GUMMOSIS CAUSED BY Phytophthora SPP. - H. N. PRAJAPATI; A. H. BARAD (The Bioscan, 2020)
Citrus is the most extensively produced tree fruit crop in the world. Citrus species are essentially diploid and were domesticated in Southeast Asia several thousand years ago and then spread throughout the world. Citrus sp. are susceptible to a number of destructive diseases that are continuously emerging and which can severely limit production or totally decimate the industries of the country. Among these citrus gummosis is one of the most important biotic constraints in the country. This study was conducted with the objective for management of citrus gummosis (.). The study of two year trial suggested that pasting the stem with metalaxyl MZ 68% WP (50 g/litre) followed by drenching of fenamidone 10% + mancozeb 50% WG, 0.2% (10 litre/ tree) twice i.e. first at onset of monsoon and second at one month after first application found effective for management of citrus gummosis.